Upaya Meningkatkan Kemampuan Representasi Matematis Siswa pada Materi Segiempat Melalui Pembelajaran Brain Based Learning di SMP IT Al-Hijrah - Fitriah Ulfa Simamora; Muhammad Badzlan Darari (Departement of Mathematics Education, 2023)
This study aims to know what effort were made to improve mathematical representation skill on quadrilateral subjects through brain based learning at smp it al-hijrah. The type of research used is Classroom Action Research. The subjects of this study is 8th grade students at smp it al-hijrah. Data collecting techniques used are test, observation and documentation. The results of this study indicate that: (1) the mathematical representation skill of 8th grade students at smp it al-hijrah being improved after applied the learning used brain based learning. (2) the improve is visible from the result score of mathematical representation skill test at the beginning of the test until cycle 2. It can be concluded that by applying learning used brain based learning can improve mathematical representation students’ skill on quadrilateral subject at SMP IT Al-Hijrah